(untitled) (London Journal of Research In Humanities and Social Sciences, 2025)
The Philippines has been grappling with a learning crisis even before the onset of the COVID-19 pandemic. This crisis worsened due to the educational disruptions brought about by the pandemic, as reflected in the 2022 PISA results. In response to these challenges and to addressing learning deficiencies while supporting recovery efforts, the Department of Education launched the National Learning Camp (NLC). Since its implementation in 2023, research on the NLC has demonstrated its effectiveness in improving student performance and engagement. However, its implementation has faced significant challenges, particularly a limited pool of teacher-volunteers due to its reliance on voluntary recruitment. This shortage has led to the deployment of out-of-field teachers, highlighting an underexplored aspect of the program.This study examines the lived experiences of out-of-field public secondary education teachers participating in the NLC within the Philippine context. Utilizing a phenomenological design, the research was conducted in a mega school in the Lapu-Lapu City Division, Cebu Region VII, Philippines. Eight out-of-field teachers were purposively selected based on the following criteria: (1) they were regular, permanent employees of the Department of Education; (2) they taught subjects in the NLC outside their areas of specialization; and (3) they had participated in the NLC at least once, ensuring familiarity with the program. Thematic analysis of their interview responses revealed four major themes: their motivations for participating in the NLC, the frustrations and challenges they encountered, their coping strategies, and their best practices in navigating the program. This study provides valuable insights into the contextual experiences of out-of-field teachers and their role in the success and sustainability of educational interventions like the NLC.